Granulocytic myeloid-derived suppressor cells increase infection risk via the IDO/IL-10 pathway in patients with hepatitis B virus-related liver failure - Yu, Xueping; Sun, Jian; Yang, Feifei; Mao, Richeng; Shen, Zhiqing; Ren, Lan; Yuan, Songhua; He, Qian; Zhang, Linxia; Yang, Yu; Ding, Xiangqing; He, Yongquan; et al. (Frontiers in Immunology, 2023)
Hepatitis B virus-related acute-on-chronic liver failure (HBV-ACLF) results in high susceptibility to infection. Although granulocytic myeloid-derived suppressor cells (gMDSC) are elevated in patients with HBV-ACLF, their role in HBV-ACLF pathogenesis is unknown. To elucidate the mechanism of gMDSC expansion and susceptibility to infection in HBV-ACLF patients, we analyzed the proportion of gMDSC in the peripheral blood and organ tissues of patients with HBV-ACLF and an ACLF mouse model established by continuous injection (eight times) of Concanavalin by flow cytometry and immunohistochemistry. We found that the proportion of gMDSC increased significantly in the blood and liver of patients with HBV-ACLF. This increase was positively correlated with disease severity, prognosis, and infection. gMDSC percentages were higher in peripheral blood, liver, spleen, and bone marrow than control levels in the ACLF mouse model. Immunofluorescence revealed that the gMDSC count increased in the liver of patients with HBV-ACLF as well as in the liver and spleen of ACLF mice. We further exposed peripheral blood monocyte cells from healthy donors to plasma from HBV-ACLF patients, recombinant cytokines, or their inhibitor, and found that TNF-α led to gMDSC expansion and significant upregulation of indoleamine 2, 3-dioxygenase (IDO), while blocking TNF-α signaling decreased gMDSC. Moreover, we detected proliferation and cytokine secretion of T lymphocytes when purified gMDSC was co-cultured with Pan T cells or IDO inhibitor and found that TNF-α-induced gMDSC inhibited T cell proliferation and interferon-γ production through the IDO signaling pathway. Lastly, the ability of gMDSC to phagocytose bacteria was low in patients with HBV-ACLF. Our findings elucidate HBV-ACLF pathogenesis and provide potential therapeutic targets.